Electrochemical deposition of La-Mg alloys in LaCl3-MgCl2-KCl system with molten salt electrolysis process - SAHOO, DEEPAK KUMAR (Journal of Mining and Metallurgy, Section B: Metallurgy, 2014)
La-Mg alloys of different compositions were prepared by electrolysis of LaCl3-MgCl2-KCl melts. Different phases of La-Mg alloys were characterized by X-ray diffraction (XRD) and Scanning Electron Microscopy (SEM). Energy dispersive spectrometry (EDS) and Inductively Coupled Plasma-Atomic Emission Spectroscopy (ICP-AES) analyses showed that chemical compositions of La-Mg alloys were consistent with phase structures of XRD pattern, and magnesium content in the alloy could be controlled by electrolysis parameters. The effects of various process parameters such as concentration of magnesium chloride in the bath, temperature of electrolysis and cathode current density on the current efficiency have  been investigated. A maximum current efficiency of 85% and yield of 80% was obtained from the bath at 12.5A/cm2 current density at an operating temp 8500C.